Hearing Loss in Facioscapulohumeral Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The clinical presentation of facioscapulohumeral dystrophy (FSHD) with unusual large 4q35 deletions was studied with attention to hearing loss.